Social indications (Marriage websites) - A field study in internet cafes (Journal of the College of Education for Women, 2019)
Marriage is considered one of the strongest ties that links between two human beings , but after the evolutions that happened in our Arab communities and specifically in the Iraqi community , marriage through the internet websites appeared . this kind of marriage is considered one of the new phenomena that appeared in the present time in many societies. That was through internet websites like yahoo , Facebook and other websites that have chat features.The Islamic sharia looks negatively at marriage through the internet announcing that this way is harmful for both the man and the woman